1996
DOI: 10.1152/jappl.1996.80.3.1065
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide effects on shortening velocity and power production in the rat diaphragm

Abstract: The present experiments tested nitric oxide (NO) effects on shortening velocity and power production in maximally activated rat diaphragm. Diaphragm fiber bundles (n = 10/group) were incubated at 37 degrees C in Krebs-Ringer solution containing no added drug (control), the NO synthase inhibitor N omega-nitro-L-arginine (L-NNA; 10 mM), the NO donor sodium nitroprusside (SNP; 1 mM), or a combination (L-NNA + SNP) Loaded shortening velocity was measured via the load-clamp technique over a range of afterloads. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 0 publications
3
52
0
Order By: Relevance
“…Our control data regarding P o , V max , and the curvature of the force-velocity relationship correspond with published values for isolated diaphragm muscle at the same experimental setup (21,48), but differ from those of Morisson et al (36) and Metzger et al (33). Factors that contribute to this variability could include difference in the temperature, animal species, and incubation time.…”
Section: Effects Of Hypoxia On Isotonic Contractile and Fatigue Propesupporting
confidence: 68%
See 4 more Smart Citations
“…Our control data regarding P o , V max , and the curvature of the force-velocity relationship correspond with published values for isolated diaphragm muscle at the same experimental setup (21,48), but differ from those of Morisson et al (36) and Metzger et al (33). Factors that contribute to this variability could include difference in the temperature, animal species, and incubation time.…”
Section: Effects Of Hypoxia On Isotonic Contractile and Fatigue Propesupporting
confidence: 68%
“…A previous study reported that NOS inhibition depressed velocity of shortening and power generation of the rat diaphragm under hyperoxic conditions in vitro (36). The NOS inhibitor N G -nitro-L-arginine, at a concentration of 10 mM, reduced V max and peak power ϳ16 and ϳ18%, respectively.…”
Section: Effects Of No On Isotonic Contractile and Fatigue Propertiesmentioning
confidence: 86%
See 3 more Smart Citations